Framing Intellectual and Lived Spaces in Early South Asia Sources and Boundaries - den Boer, Lucas; Cecil, Elizabeth A. (Beyond Boundaries, 2020)
The contributions to this book address a series of ´confrontations`-debates between intellectual communities, the interplay of texts and images, and the intersection of monumental architecture and physical terrain-and explore the ways in which the legacy of these encounters, and the human responses to them, conditioned cultural production in early South Asia (c. 4th-7th centuries CE).